FACTORS OF GESTATION HYPERTENSION PATHOGENESIS - N. A. Konyshko; T. E. Morosova (Российский кардиологический журнал)
The review focuses on the opinions of scientists and on the results of studies of molecular mechanisms in gestation hypertension pathogenesis as on the influence of social, psychosomatic and anamnestic factors on the stages of this pathology development.